Teaching and learning qur'anic Arabic utilizing adaptive and intelligent systems for collaborative learning (EDW B13-084-0969) - Pathan, Al-Sakib Khan; Abdullah , Matin Saad; Al Shaikhli, Imad Fakhri (RMC, IIUM, 2015)
About 80 percent of the world's Muslim populations are non-native speakers of the Arabic language. Since ‎it ‎is ‎‎obligatory for all Muslims to recite the Qur'an in Arabic ‎during regular prayers, ‎an ‎extraordinary ‎‎social phenomenon has taken place ‎in some parts of the ‎Muslim ‎world: Muslims, men and women, learn the complex phonological rules of the Arabic language in the context of the Qur'an and recite the "sounds" of the Qur'an often understanding very little of what they are reciting. This has given rise to a Muslim demographic segment of adult learners whose main learning goal is to recall an idiomatic translation while reading or listening to the Qur'an. Despite the availability of conventional resources for this purpose, according to our detailed investigation, no empirical research has explored the possibilities of emerging adaptive and intelligent systems for collaborative learning to address this challenge. The goals of this research are: (a) to determine the applicability of learner corpus research through automated pattern extraction from available Qur'anic corpora (b) to investigate declarative memory modeling approaches in order to develop a quantitative algorithm to maximize learning and (c) to explore the possibilities of utilizing existing social networks to enhance learner motivation.